Staged Endovascular Intervention for Axillary Artery Aneurysm Complicated by Recurrent Upper Limb Arterial Embolism: A Case Report - Xiaolong Li; Yayun Xiao; Yulin Zhang; Liwei Zhang; Qunfeng Liu (Clinical Case Reports, 2026)
ABSTRACT Axillary artery aneurysm is an uncommon subtype of peripheral arterial aneurysm, and mural thrombus within the aneurysm sac frequently dislodges to trigger recurrent refractory acute upper extremity arterial embolism. This study reports a 57‐year‐old male patient who suffered immediate re‐embolization after isolated percutaneous thrombus aspiration. A staged endovascular strategy consisting of thrombus aspiration, catheter‐directed thrombolysis and covered stent graft implantation was adopted for radical treatment. Perioperative angiography and 2‐month follow‐up computed tomography angiography (CTA) confirmed complete thrombus clearance, aneurysm exclusion and sustained unobstructed distal limb perfusion. This staged minimally invasive protocol addresses both acute distal ischemia and the embolic source at the aneurysm, providing a safe and replicable reference for managing similar complex cases.